Rheological characterization of water atomised stainless steel powder for micro metal injection molding - Ibrahim, Mohd. Halim Irwan; Muhamad, Norhamidi; Sulong, A. B.; Jamaludin, Khairur Rijal; Mohamad Nor, Nor Hafiez; Ahmad, Sufizar (2009)
In this paper, the performance of feedstock characteristics for micro metal injection molding (µMIM) is investigated by optimum power loading variation and rheological characterization. Due to the highly stringent characteristics of µMIM’s feedstock, the study has been emphasized on the powder and binder system in which stainless steel SS316L powder are mixed with composite binder, which consists of PEG (Polyethelena Glycol), PMMA (Polymethyl Methacrilate) and SA (Stearic Acid) by variation of powder loading concentration. The rheology properties are investigated using Shimadzu Flowtester CFT-500D capillary rheometer. The geometry of water atomised stainless steel powder are irregular shape, therefore it is expected significant changes in the rheological results that can influence the microcomponent, surface quality, shape retention and resolution capabilities. The optimization of the µMIM rheological properties as a function of stainless steel powder loading concentration are evaluated by flow behavior exponent, activation energy and moldability index. Results show that 61.5%vol contributes a significant stability over a range of temperature and the best powder loading from a critical powder volume percentage (CPVP) and rheological point of view